Fast Simulation of Mitral Annuloplasty for Surgical Planning - Tenenholtz, Neil A. (Funct Imaging Model Heart, 2013)
Mitral valve repair is a complex procedure that requires the ability to predict closed valve shape through the examination of an unpressurized, accid valve. These procedures typically include the remodeling of the mitral annulus through the insertion of an annuloplasty ring. While simulations could facilitate the planning of the procedure, traditional finite-element models of mitral annuloplasty are too slow to be clinically feasible and have never been validated in tissue. This work presents a fast method for simulating valve closure post-annuloplasty using a mass-spring tissue model and subject-specific valve geometry. Closed valve shape is predicted in less than one second. The results are validated by implanting an annuloplasty ring in an excised porcine heart and comparing simulated to imaged results. Results indicate that not only can mitral annuloplasty be simulated quickly, but also with submillimeter accuracy.